2009
DOI: 10.1182/blood-2008-09-178178
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen variant BβD432A has normal polymerization but does not bind knob “B”

Abstract: Fibrinogen residue B␤432Asp is part of hole "b" that interacts with knob "B," whose sequence starts with Gly-His-ArgPro-amide (GHRP). Because previous studies showed B␤D432A has normal polymerization, we hypothesized that B␤432Asp is not critical for knob "B" binding and that new knob-hole interactions would compensate for the loss of this Asp residue. To test this hypothesis, we solved the crystal structure of fragment D from B␤D432A. Surprisingly, the structure (rfD-B␤D432A؉GH) showed the peptide GHRP was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Experiments with a variant fibrinogen, BβD432A, indicate that ‘B:b’ interactions per se influence the rate of clot lysis. This variant cannot form ‘B:b’ interactions, but the BβD432A fibrin network measured by turbidity and SEM is indistinguishable from normal 66. Nevertheless, lysis of BβD432A fibrin is enhanced relative to normal 67…”
Section: Fibrin Stabilitymentioning
confidence: 91%
“…Experiments with a variant fibrinogen, BβD432A, indicate that ‘B:b’ interactions per se influence the rate of clot lysis. This variant cannot form ‘B:b’ interactions, but the BβD432A fibrin network measured by turbidity and SEM is indistinguishable from normal 66. Nevertheless, lysis of BβD432A fibrin is enhanced relative to normal 67…”
Section: Fibrin Stabilitymentioning
confidence: 91%
“…The D:D interface, which contains residues γ275–309 (Everse et al, 1998) is weak, yielding first to a pulling force upon stretching of fibrin(ogen) oligomers (Zhmurov et al, 2011, 2012). Studies of point mutations revealed that residues γ275, γ308, and γ309 are essential for D-D interactions and elongation of fibrin strands (Hirota-Kawadobora et al, 2004; Marchi et al, 2006; Bowley and Lord, 2009). Fibrin monomers can add longitudinally to form protofibrils, two-stranded oligomers that reach a certain length to begin lateral aggregation (Hantgan et al, 1980; Fowler et al, 1981; Medved et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…12 On the other hand, fibrinogen variant BbD432A with impaired hole 'b' displays normal polymerization. 13 Therefore, it appears that B:b bonds can occur at least when A:a interactions are compromised, but their normal functional role is still mostly unknown. It is possible that B:b binding has an effect on the susceptibility of a clot to enzymatic destruction.…”
Section: Knob-hole Interactionsmentioning
confidence: 99%